Confining the spin between two metal atoms within the carbon cage: redox-active metal–metal bonds in dimetallofullerenes and their stable cation radicals. Issue 23 (2nd June 2017) - Samoylova, Nataliya A.; Avdoshenko, Stanislav M.; Krylov, Denis S.; Thompson, Hannah R.; Kirkhorn, Amelia C.; Rosenkranz, Marco; Schiemenz, Sandra; Ziegs, Frank; Wolter, Anja U. B.; Yang, Shangfeng; Stevenson, Steven; Popov, Alexey A.
Abstract : Dimetallofullerenes are reversibly oxidized giving a single-electron metal–metal bond with unusual spin properties. Abstract : Lanthanide–lanthanide bonds are exceptionally rare, and dimetallofullerenes provide a unique possibility to stabilize and study these unusual bonding patterns. The presence of metal–metal bonds and consequences thereof for the electronic properties of M2 @C82 (M = Sc, Er, Lu) are addressed by electrochemistry, electron paramagnetic resonance, SQUID magnetometry and other spectroscopic techniques. A simplified non-chromatographic separation procedure is developed for the isolation of Er2 @C82 ( C s (6) and C 3v (8) cage isomers) and Sc2 @C82 ( C 3v (8) isomer) from fullerene mixtures. Sulfide clusterfullerenes Er2 S@C82 with C s (6) and C 3v (8) fullerene cages are synthesized for the first time. The metal–metal bonding orbital of the spd hybrid character in M2 @C82 is shown to be the highest occupied molecular orbital, which undergoes reversible single-electron oxidation with a metal-dependent oxidation potential. Sulfide clusterfullerenes with a fullerene-based HOMO have more positive oxidation potentials. The metal-based oxidation of Sc2 @C82 - C 3v is confirmed by the EPR spectrum of the cation radical [Sc2 @C82 - C 3v ] + generated by chemical oxidation in solution. The spectrum exhibits an exceptionally large a ( 45 Sc) hyperfine coupling constant of 199.2 G, indicating a substantial 4s contribution to the metal–metal bonding orbital. The cationic salt [Er2 @C82 - C 3v ] + SbCl6 − is prepared, and its magnetization behavior is compared to that of pristine Er2 @C82 - C 3v and Er2 S@C82 - C 3v . The formation of the single-electron Er–Er bond in the cation dramatically changes the coupling between magnetic moments of Er ions.